Social Transformation through Day Care and Home Care: A Study of Empowering People with Mental Retardation - Ulya Afif, Yusmicha; Syakirin, Ahmad (MUHARRIK: Jurnal Dakwah dan Sosial, 2024)
This article examines community-based empowerment practices for persons with intellectual disabilities through the Day Care and Home Care programmes implemented by Rumah Kasih Sayang Ponorogo. Framed within the perspective of da‘wah as social transformation, the study focuses on how integrated care models contribute to mental health improvement, social inclusion, and the reduction of stigma within marginalized rural communities. Employing a qualitative case study approach, data were collected through in-depth interviews, participant observation, and document analysis involving programme managers, volunteers, families, and community stakeholders in the villages of Krebet and Sidoharjo, Ponorogo. The findings demonstrate that the dual-service model—combining institution-based day care for individuals with mild intellectual disabilities and home-based care for those with severe conditions—functions as a holistic empowerment mechanism encompassing physical health support, psychosocial education, spiritual guidance, skills training, and productive economic assistance. These interventions not only enhance individual mental resilience and functional independence but also foster greater family participation and community acceptance. Importantly, the programmes contribute to a gradual transformation of social perceptions, weakening long-standing stigmatization of persons with intellectual disabilities as a social burden. This study argues that the effectiveness of Rumah Kasih Sayang’s model lies in its community-embedded, humanistic, and participatory approach, which aligns social care with values of compassion, empowerment, and inclusivity central to transformative da‘wah. Nevertheless, the research also identifies structural challenges related to sustainability, funding limitations, and uneven service coverage. The article concludes by emphasizing the need for stronger institutional synergy and policy support to ensure the long-term viability of community-based empowerment initiatives for persons with intellectual disabilities.